From "Explicit" to "Implicit" in Recent Religious Art. (16th February 2016) - Howes, Graham
Abstract : This essay questions today's implicit cultural assumption that Western Christianity continues to provide a cultural and credal framework within which the relationship between art and religion is acted out. It argues instead that today's artists are unlikely to be keyed into religious culture because there is no longer any identifiable religious culture for them to be keyed into. The reasons for this are explored, and include secularization (however problematically defined), an increasing transition from a religious to an aesthetic validation of experience, post-modernity and its so-called "crisis in representation, " and the increasingly second-order status of the visual within at least the Western Christian tradition. Yet this scenario does not necessarily predicate terminal decline. Instead it is argued that today's artists are more likely to disclose the implicitly numinous rather than the explicitly incarnational, offering us generalized religious experience rather than Christian revelation, hence moving religious art beyond its traditionally didactic and narrative parameters, and firmly towards the primarily experiential. Such art does more than provide undemanding spiritual massage for Christians and post-Christians alike. It may also "democratise" religious art and widen public access to the transcendent. Drawing specifically on the work of Bill Viola, Anthony Gormley and the late Craigie Aitchison, several mixed, if not necessarily conflicting messages emerge—a cultural mutation way from "religion" and towards "spirituality, " a transition from a narrowly and exclusively Christian art towards what one critic calls "works which are only implicitly religious in their inspiration and so without identifiable religious themes and traditional symbols, " and, above all, evidence of today's "religious" artists increasingly seeking for meaning within themselves rather than from the supernatural stories or rituals of institutional churches. In this sense they provide an aesthetic response to Edward Bailey's own enticing "Invitation One" when operationalising the concept of "Implicit Religion" i.e. "to relate religion, consciousness and experience."